The Induction of High-Frequency Callus with an Elite Cotton (Gossypium Hirsutum L.) from Côte d’Ivoire: Callogenesis in cotton - N’GUESSAN, Affoué Sylvie Rachelle; AYOLIE, Koutouan; YAPO, Sopie Edwige Salomé; KONAN, Yao Kouakou Francois; N’CHO, Achi Laurent; N’GORAN, Kouakou Désiré; KONE, Dramane; KOUADIO, Yatty Justin; KOUAKOU, Tanoh Hilaire (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2019)
In cotton, factors such as carbon sources, hormonal combination, and type of explant influence the responses to callus induction. In this study callus induction was optimized to get high-frequency callus in cotton. Different carbon sources were tested, and among them, glucose at 3% was found to be the best carbohydrate in callus induction. Culture medium supplemented with 2,4-D (0.1 mg.L-1) and KIN (0.5 mg.L-1) gave a high callogenesis response, unlike other hormonal combinations. With explants, hypocotyl (72.93%) appeared easier to induce callus than cotyledon (48.75%) following root (37.5%). So, carbone sources, hormone, and their concentration affect significantly callus induction. The highest frequency of callus induction was then observed when hypocotyl explants were cultured on medium supplemented with 0.1 mg.L-1 of 2,4-D in combination with 0.5 mg.L-1 of KIN and 3% glucose. The induced-callus obtained were friable and of high quality. The other types of combinations resulted in the formation of compact callus with sometimes roots emerging from it. The present study may provide an efficient protocol to improve the callogenesis responses by adjusting the carbohydrates, the hormonal regime, and the type of explant to be cultured for a high-frequency callus induction of the Y331B-R5 cotton cultivar.